Investigation on a No Trial Weight Spray Online Dynamic Balancer - Xialun Yun; Xuesong Mei; Gedong Jiang; Zhenbang Hu; Zunhao Zhang (Shock and Vibration)
In order to suppress the spindle vibration with high efficiency and high precision, a no without trial weight spray online balance method is proposed in this paper. By analyzing the relationship between the unbalanced excitation and the unbalanced response of the spindle, the relationship between the dynamic influence coefficient and the system model is studied. A high-speed spindle finite element analysis model was established, and the dynamic influence coefficient matrix was identified. A no trial weight spray online dynamic balancing system was developed, which has the advantages of without trial weight and high-precision loading. A new type of integrated balancing terminal that was formed using 3D printing technology was first proposed by our research group, and its advantages in various aspects are significantly higher than traditional assembly balanced terminals. The experimental verification of the without trial weight spray online dynamic balancing system was performed on a high-speed spindle test stand. Experiments show that the no trial weight spray online balancing method proposed in this paper can achieve high-efficiency and high-precision vibration suppression, greatly reducing balance time and cost of the spindle. At the same time, the online balance test also verified the reliability of the integrated balanced terminal.